Toll‐like receptor‐9 in Spanish multiple sclerosis patients: an association with the gender. (4th June 2013) - Dominguez‐Mozo, M. I.; Garcia‐Montojo, M.; López‐Cavanillas, M.; De, V.; Garcia‐Martinez, A.; Arias‐Leal, A. M.; Casanova, I.; Urcelay, E.; Arroyo, R.; Alvarez‐Lafuente, R.
<x xml:space="preserve">Abstract</x> Background and purpose Toll‐like receptor‐9 (TLR9) is a potent inducer of innate immune system triggered by infection with viruses, some of them previously related to multiple sclerosis (MS). The aim of this study was to analyze the possible association of two TLR9 single nucleotide polymorphisms (SNPs; rs352162 and rs187084) with susceptibility to MS. Methods Two independent cohorts of MS patients and controls were included: 574 clinically definite relapsing‐remitting MS patients (367 females) and 807 healthy controls (418 females) for the first cohort; and 366 relapsing‐remitting MS patients (238 females) and 224 healthy controls (160 females) for the second cohort. Genotyping was performed by TaqMan assays. Results The AT haplotype was found to be significantly higher in women than in men (P = 0.013 and P = 0.044). Conclusions Here two possible genetic markers are proposed that could be also associated with the differences observed in the clinical course of MS in both genders. Further studies with larger cohorts should be performed to confirm these results.